Automated GMP compliant production of [18F]AlF-NOTA-octreotide - Térence Tshibangu; Christopher Cawthorne; Kim Serdons; Elin Pauwels; Willy Gsell; Guy Bormans; Christophe M. Deroose; Frederik Cleeren (SpringerOpen, 2020)
Abstract Background Gallium-68 labeled synthetic somatostatin analogs for PET/CT imaging are the current gold standard for somatostatin receptor imaging in neuroendocrine tumor patients. Despite good imaging properties, their use in clinical practice is hampered by the low production levels of 68Ga eluted from a 68Ge/68Ga generator. In contrast, 18F-tracers can be produced in large quantities allowing centralized production and distribution to distant PET centers. [18F]AlF-NOTA-octreotide is a promising tracer that combines a straightforward Al18F-based production procedure with excellent in vivo pharmacokinetics and specific tumor uptake, demonstrated in SSTR2 positive tumor mice. However, advancing towards clinical studies with [18F]AlF-NOTA-octreotide requires the development of an efficient automated GMP production process and additional preclinical studies are necessary to further evaluate the in vivo properties of [18F]AlF-NOTA-octreotide. In this study, we present the automated GMP production of [18F]AlF-NOTA-octreotide on the Trasis AllinOne® radio-synthesizer platform and quality control of the drug product in accordance with GMP. Further, radiometabolite studies were performed and the pharmacokinetics and biodistribution of [18F]AlF-NOTA-octreotide were assessed in healthy rats using μPET/MR. Results The production process of [18F]AlF-NOTA-octreotide has been validated by three validation production runs and the tracer was obtained with a final batch activity of 10.8 ± 1.3 GBq at end of synthesis with a radiochemical yield of 26.1 ± 3.6% (dc), high radiochemical purity and stability (96.3 ± 0.2% up to 6 h post synthesis) and an apparent molar activity of 160.5 ± 75.3 GBq/μmol. The total synthesis time was 40 ± 3 min. Further, the quality control was successfully implemented using validated analytical procedures. Finally, [18F]AlF-NOTA-octreotide showed high in vivo stability and favorable pharmacokinetics with high and specific accumulation in SSTR2-expressing organs in rats. Conclusion This robust and automated production process provides high batch activity of [18F]AlF-NOTA-octreotide allowing centralized production and shipment of the compound to remote PET centers. Further, the production process and quality control developed for [18F]AlF-NOTA-octreotide is easily implementable in a clinical setting and the tracer is a potential clinical alternative for somatostatin directed 68Ga labeled peptides obviating the need for a 68Ge/68Ga-generator. Finally, the favorable in vivo properties of [18F]AlF-NOTA-octreotide in rats, with high and specific accumulation in SSTR2 expressing organs, supports clinical translation.